Risk factors for acute and overuse sport injuries in Swedish children 11 to 15 years old: What about resistance training with weights? - Boström, A.; Thulin, K.; Fredriksson, M.; Reese, D.; Rockborn, P.; Hammar, M. L. (Scandinavian Journal of Medicine & Science in Sports, 2016)
To determine the 1-year self-reported incidence of overuse and traumatic sport injuries and risk factors for injuries in children participating in a summer sports camp representing seven different sports. 4363 children, 11 to 15 years old participating in a summer camp in seven different sports answered a questionnaire. Injury in this cross-sectional study was defined as a sport-related trauma or overload leading to pain and dysfunction preventing the person from participation in training or competition for at least 1 week. A number of risk factors for injury were investigated such as sex, age, number of hours spent on training in general, and on resistance training with weights. Nearly half [49%, 95% confidence interval (CI) 48-51%] of the participants had been injured as a result of participation in a sport during the preceding year, significantly more boys than girls (53%, 95% CI 50-55% vs 46%, 95% CI 43-48%; P < 0.001). Three factors contributed to increased incidence of sport injuries: age, sex, and resistance training with weights. Time spent on resistance training with weights was significantly associated with sport injuries in a logistic regression analysis. In children age 11 to 15 years, the risk of having a sport-related injury increased with age and occurred more often in boys than in girls. Weight training was the only modifiable risk factor that contributed to a significant increase in the incidence of sport injuries.